2017
DOI: 10.1111/rec.12639
|View full text |Cite
|
Sign up to set email alerts
|

A field test of commercial soil microbial treatments on native grassland restoration

Abstract: Seedling establishment and performance are often limiting steps in many grassland restorations. The soil microbial community is thought to be a factor that contributes to the poor performance of seedlings. Therefore, we conducted a field test to examine the ability of four treatments to alter the soil microbial community and improve seedling performance during restoration. Treatments were commercially available bacterial inoculum, fungal inoculum, fungicide, and a bacteria/fungicide combination which were all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…While the above research highlights improvements in restoration response to native mycorrhizae, restoration outcomes have been shown to benefit less from commercial mycorrhizal inoculum products. Late successional plants have been shown to be inhibited by commercial fungi (Middleton et al ; Emam ) and commercial fungi have been shown to have little effect on reducing soil erosion (Vogelsang & Bever ), native plant richness (Perkins & Bennett ), or cover (White et al ; Ohsowski et al ). Commercial inoculum products may fail because many AM fungal species that are commercially available are likely highly abundant in disturbed, post‐agricultural, and early successional soils (Koziol et al ).…”
Section: Introductionmentioning
confidence: 99%
“…While the above research highlights improvements in restoration response to native mycorrhizae, restoration outcomes have been shown to benefit less from commercial mycorrhizal inoculum products. Late successional plants have been shown to be inhibited by commercial fungi (Middleton et al ; Emam ) and commercial fungi have been shown to have little effect on reducing soil erosion (Vogelsang & Bever ), native plant richness (Perkins & Bennett ), or cover (White et al ; Ohsowski et al ). Commercial inoculum products may fail because many AM fungal species that are commercially available are likely highly abundant in disturbed, post‐agricultural, and early successional soils (Koziol et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil conditions may also be addressed more directly by influencing soil chemical and physical factors, such as increasing soil organic matter ( Viall et al 2014 ) or by inoculating soils with microbial communities ( Johnson 1998 ). The latter has shown promise in some grassland circumstances ( Rowe et al 2007 ;Perkins and Bennett 2018 ;Rowe et al 2009 ;Middleton and Bever 2012 ;Emam 2016 ), although responsiveness varies among species. Including arbuscular mycorrhizal fungi during site preparation and seeding has also shown promise in promoting the recovery of desirable grassland plant species ( Koziol and Bever 2017 ), but these methods are still in development.…”
Section: Soil Conditionsmentioning
confidence: 99%
“…In addition to drought-stress tolerance, studies have found promising results by using AMF and other biofertilizers to reduce environmental stresses such as salinity and heavy metal accumulations [ 22 , 23 , 24 ]. Due to this, AMF have been gaining interest and are regularly used as a restoration tool, particularly in forested systems [ 25 , 26 , 27 , 28 ]. AMF can be particularly important in ecosystems with a history of disturbance with a degraded local AMF propagule density [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%